Survey: Proactive and Reactive Routing Protocols - G, Prapulla; Kumar, Prasanna M (International Journal of Computer Sciences and Engineering, 2025)
Routing is a mechanism to build links or connections between two or more nodes with or without the infrastructure. A Routing algorithm is a method for determining the routing of packets in a node. For each node of network, the algorithm determines a routing table, which in each destination, matches an output line. The algorithm should lead to a consistent routing, that is to say without loop. This means that you should not route a packet a node to another node that could send back the package.There are three main types of routing algorithms- Vector (distance-vector routing),To link state (link state routing), Path to vector (pathvector routing).This paper focus on the survey of reactive and proactive routing protocols like OLSR, AODV, RIP, OSPF, DSR.